Characterization of antigenic determinants in the core antigen of the hepatitis C virus - Goeser, Tobias; Müller, Hubert M.; Ye, Jin; Pfaff, Eberhard; Theilmann, Lorenz (Virology, 1994)
Antibodies to the hepatitis C virus (HCV) core protein are present in the majority of patients with chronic HCV infection. To characterize the corresponding determinants, synthetic peptides and various deletion clones of the core gene expressed in Escherichia coli were used to test human anti-core positive sera or rabbit anti-peptide antibodies in enzyme-linked immunosorbent assays, immunoblots, and competition assays. Two distinct linear antigenic determinants which are located within aa 1 to 20 and between aa 30 and 47 were found. Further studies using reactive serum after preabsorption of antibodies with N- and C-terminal-deleted HCV core proteins or with peptides directed to the linear epitopes revealed an additional determinant that requires for presentation the participation of the N-terminal 69 amino acids. It is postulated that the HCV core protein forms a three-dimensional structure exposing two linear epitopes and, in addition, presents a conformational determinant within the N-terminal 69 amino acids. The remaining core amino acid sequence spanning from position 69 to 191 does not seem to expose further determinants to induce additional anti-core antibodies.